Methodical Support for Postgraduate Students - Михайловна Стручаева, Тамара (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The article presents the Belgorod region experiment in working with gifted postgraduate students and describes the methodical support directions during their postgraduate professional activity.